PENGARUH E-SERVICE QUALITY, E-SATISFACTION DAN E-TRUST TERHADAP CUSTOMER LOYALITY PENGGUNA APLIKASI MOBILE KAI ACCESS (Studi pada pengguna Aplikasi Mobile KAI Acces Semarang) - Dewi Nurayni; Widiartanto Widiartanto (Universitas Diponegoro, 2019)
The purpose of this study is to determine the effect of e-service quality, e-satisfaction, e-trust and customer loyalty variables. The population is all of the KAI Access mobile application users in Semarang, using a sampling technique sampling pusposive to 100 respondents. The type of this research is explanatory researchThe analysis that is used is path analysis, where previously the validity test, reliability test, correlation coefficient test, coefficient of determination, simple regression analysis, and significance test (t test and sobel test). The result of the study shows that e-service quality, e-satisfaction, e-trust and customer loyalty have positive effects on the customer loyalty. Based on the path analysis, it shows that e-service quality variable can affect the customer loyalty variable can have a greater effect by means of e-satisfaction and e-trust variables first. So that, it can be said that e-satisfaction and etrust variables are an intervening variable between e-service quality and customer loyalty variables. Based on these results, there are several suggestions that can be done by KAI Access; namely pay attention to the stability of the KAI Access application server and the company is expected to be able to maintain the quality of the application server, and be able to meet consumer needs.